Experimental validation of damping properties and solar pressure effects on flexible, high area-to-mass ratio debris model. (September 2017) - Channumsin, Sittiporn; Ceriotti, Matteo; Radice, Gianmarco; Watson, Ian
Abstract: Multilayer insulation (MLI) is a recently-discovered type of debris originating from delamination of aging spacecraft; it is mostly detected near the geosynchronous orbit (GEO). Observation data indicates that these objects are characterised by high reflectivity, high area-to-mass ratio (HAMR), fast rotation, high sensitivity to perturbations (especially solar radiation pressure) and change of area-to-mass ratio (AMR) over time. As a result, traditional models (e.g. cannonball) are unsuitable to represent and predict this debris' orbital evolution. Previous work by the authors effectively modelled the flexible debris by means of multibody dynamics to improve the prediction accuracy. The orbit evolution with the flexible model resulted significantly different from using the rigid model. This paper aims to present a methodology to determine the dynamic properties of thin membranes with the purpose to validate the deformation characteristics of the flexible model. A high-vacuum chamber (10 −4 mbar) to significantly decrease air friction, inside which a thin membrane is hinged at one end but free at the other provides the experimental setup. A free motion test is used to determine the damping characteristics and natural frequency of the thin membrane via logarithmic decrement and frequency response. The membrane can swing freely in the chamber and the motion is tracked by a static, optical camera, and a Kalman filter technique is implemented in the tracking algorithm to reduce noise and increase the tracking accuracy of the oscillating motion. Then, the effect of solar radiation pressure on the thin membrane is investigated: a high power spotlight (500–2000 W) is used to illuminate the sample and any displacement of the membrane is measured by means of a high-resolution laser sensor. Analytic methods from the natural frequency response and Finite Element Analysis (FEA) including multibody simulations of both experimental setups are used for the validation of the flexible model by comparing the experimental results of amplitude decay, natural frequencies and deformation. The experimental results show good agreement with both analytical results and finite element methods. Highlights: The experimental methodologies to validate the flexible HAMR debris model based on multibody dynamics are presented. The object tracking technique is modified to determine the dynamic properties and natural frequency of a thin membrane. The correct dynamic properties and reflection properties directly effect to the accuracy of the mechanical dynamic model. The numerical results of the multibody model are coherent with both results of the experiments and finite element analysis. The deformation accuracy due to a radiation pressure can be improved by compensating the reflection properties.